Sydenham's Chorea Therapy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Five patients with chorea successfully treated with carbamazepine at plasma levels of 6.5 - 8.8 mcg/ml are reported from the Dept of Pediatrics, Child Neurology and EEG Service, Hospital Infantil Vall d'Hebron, Autonomous University, Barcelona, Spain.